Metode Fitoremediasi Dalam Pengelolaan air Tercemar Logam Timbal (Pb) dan Kromium (Cr) Berdasarkan Literatur Review - Leka, Emil (Universitas Bojonegoro, 2024)
Heavy metals (HM) are metals with high density and high electrical conductivity. It is an important part of the earth's crust and appears in our environment through natural (volcanoes, springs) and human activities (use of fossil fuels, agriculture and industry). The high sulfate and metal content in acid mine drainage causes significant environmental damage, requiring special treatment. Almost all industrial waste contains heavy metals. More industry will increase pollution of water sources due to industrial waste. The purpose of this research is as a reference in analyzing plant types that quickly absorb the heavy metals Lead (Pb) and Chromium (Cr) in water using the phytoremediation method. It is hoped that acid mine drainage management methods that are easy to use, cheap and environmentally friendly will be implemented for sustainable development. One of the rehabilitation techniques for AAT polluted environments is phytoremediation. Phytoremediation is the most effective method for managing acid mine drainage. The research results show that several plants are very effective and significant in helping the absorption of the heavy metals Lead (Pb) and Chromium (Cr) contained in acid mine drainage. The research results showed that water spinach (Ipomea Aquatic) 95.8% and water jasmine (Echinodorus Palaefolius) 92.5% were the most suitable plants for the phytoremediation method when controlling acid mine drainage.